The Position of Humans as Creatures with Thoughts: Philosophical Perspectives and the Emergence of Artificial Intelligence (AI) in the World of Education - Zikri Rahman; Akhmad Fauzi Hamzah (Al-Munawwarah: Journal of Islamic Education, 2025)
The rapid advancement of technology, particularly artificial intelligence (AI), has profoundly transformed the landscape of education, prompting vital questions regarding the role of human educators in the teaching and learning process. As educational institutions increasingly integrate AI-driven tools, the challenge of incorporating moral and ethical values within the framework of Islamic education becomes increasingly pressing in this digital age. This study aims to explore the intricate relationship between humans as rational beings and the influence of AI in educational practices, with a particular emphasis on Islamic perspectives. Utilizing a qualitative research method, the research employs a literature review approach to analyze a variety of relevant scholarly sources. The findings reveal that while AI has the potential to significantly enhance learning efficiency through personalized learning experiences and data-driven insights, the indispensable role of human educators persists in guiding students' character formation and moral development. Furthermore, effective education extends beyond mere knowledge transfer; it encompasses the nurturing of values and ethics that prepare students for responsible citizenship. Ultimately, these findings offer new insights into how the collaboration between human educators and AI technology can foster a more enriching educational environment aligned with the principles of Islamic education, ensuring that moral and ethical considerations remain central to the learning experience.